Effects of Ultrasound on Spoilage Microorganisms, Quality, and Antioxidant Capacity of Postharvest Cherry Tomatoes. Issue 10 (16th September 2015) - Wang, Wenjun; Ma, Xiaobin; Zou, Mingming; Jiang, Peng; Hu, Weixin; Li, Jiao; Zhi, Zijian; Chen, Jianle; Li, Shan; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: Mature‐green cherry tomato fruits ( Lycopersicon esculentum cv. Jinyu) were exposed to different power densities of ultrasound (66.64, 106.19, and 145.74 W/L) at 25 °C to study ultrasound non‐thermal effects on the storage properties. Among the three levels of ultrasound irradiation, 106.19 W/L ultrasound was effective in reducing the spoilage microorganisms, delaying postharvest ripening through inhibiting ethylene production and respiration rates, and consequently maintaining fruit firmness, flavor, enzyme activities, antioxidants (total phenolics, total flavonoids), and the total antioxidant capacity of cherry tomatoes. The 66.64 W/L ultrasound had similar effects but to a lesser extent. Meanwhile, although 145.74 W/L ultrasound resulted in higher content of ascorbic acid (AA), it showed many negative effects on the storage quality of fruits. These results demonstrated that ultrasound of appropriate power density had great potentials in inhibiting decay, maintaining flavor and nutritional quality of cherry tomatoes.